Ginásio Clube Português (GCP) : measuring customer satisfaction in services industry - Alves, Guilherme Fernandes Rito (2015)
The objective of this thesis is to measure and analyze the customer satisfaction level in Ginásio Clube Português, by understanding the key determinants and consequences of customer satisfaction. After an exponential growth both in revenues and in number of clients between 1998 and 2011, Ginásio Clube Português is losing competitive edge due to the increasing competition in the high-end and low-cost markets as well as due to the effects of the economic downturn. Aiming to ensure that revenues are greater than costs as well as to increase the market share in the Portuguese fitness industry, José Carlos Reis (CEO) is adopting cost containment policies since it has been difficult to raise revenues and, at the same time, investing in a market expansion growth strategy, often called market development strategy. With these purposes in mind, José Carlos Reis would like to know which is the effect of the satisfaction of the most valuable asset of the company, the client, on GCP’s financial performance as well as its effect in other metrics as: service quality, service value, customer loyalty and word of mouth. Bearing in mind the literature review, in order to be successful in the market is not sufficient to attract new customers. José Carlos Reis must concentrate in retaining existing ones, through the implementation of effective policies of customer satisfaction and loyalty which will result in a greater profitability for the business and sustainability in the future. The main conclusions drawn from this study are the following: first, clients with a high physical activity level in GCP are more satisfied. Second, perceived service quality and perceived service value have a direct positive effect on customer satisfaction in GCP. Last but not least, customer satisfaction has a direct positive impact on customer loyalty and word-of-mouth.